Pengembangan Kualitas Service Toko Bagus Sidoarjo menggunakan Sistem Informasi Penjualan berbasis Web - M. Fahmi Aresha; Fajar Pradana; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Toko Bagus is one of the bicycle shops in Sidoarjo Regency that provides service, sales of bicycles and sales of bicycle spare parts. Currently, Toko Bagus already has a Sales Information System, but it still has some drawbacks, namely not having a frontend website. Whereas on the backend website there is no feature for ordering goods from suppliers. There is no supplier goods receipt report feature and actor access rights in the system. Therefore, a website-based Sales Information System was built which was the development of the previous Information System.The process of developing this Information System uses the waterfall model SDLC. The stages are literature study, data collection, requirements engineering, system design, implementation, testing, and drawing conclusions and suggestions. In the needs engineering stage, the Bagus Sidoarjo Store Sales Information System has 28 functional requirements and 1 non-functional requirement. architectural design, component design, data design, and interface design. At the testing stage using white-box testing and black-box testing methods. In white-box testing using the basis path testing method which is carried out on the 3 main functions of the system, then in black-box testing using user acceptance testing (UAT) it produces a value of 89% for the admin actor and a value of 90% for the owner actor.